Electrostatics facilitate midair host attachment in parasitic jumping nematodes - Ranjiangshang Ran; Justin C. Burton; Sunny Kumar; Saad Bhamla; Adler R. Dillman; Victor M. Ortega-Jimenez (Proceedings of the National Academy of Sciences, 2025)
Jumping can be hazardous for entomopathogenic nematodes (EPNs) as those that fail to attach to an insect host face death by predation or starvation. Recently, it has been shown that electrostatic charges on large insects can prompt a close-range detachment of free-living nematodes, which are nonparasitic and unable to jump. However, it remains unclear if static electricity can influence aerial interactions between parasitic jumping worms and their insect hosts. Here, we analyze and model the trajectories of jumping EPNs in still air as they approach fruit flies with varying electrostatic charge. We find that the nematodes’ attachment to the host is facilitated by an electrical potential of a few hundred volts, a magnitude commonly found in flying insects. A model combining electrostatics, aerodynamics, and Bayesian inference indicates that the electrostatic charge on jumping nematodes is ∼ 0.1 pC, which aligns with theoretical predictions for electrostatic induction. Drag coefficients based on host–nematode interactions in the presence of horizontal wind show differences at both low and high jumping velocities. Numerical simulations show that intermediate wind speeds ( ∼ 0.2 m/s) can further increase the likelihood of host attachment, as wind-driven aerial drifting allows the worms to reach hosts at greater distances. Our results suggest that submillimeter parasites that become airborne may exploit the electric charge carried by their host to facilitate attachment and thus enhance survival. The use of quantitative physical models provides valuable insights into understanding complex airborne infectious diseases mediated by natural environmental forces.